Khilafah Islam dalam Perspektif Sejarah Pemikiran Ali Abdul Raziq - Syahrudin Siregar (UIN Sumatera Utara Medan, 2018)
Ali Abdul Raziq is a scholar from Egypt. He was born in 1888. His famous thought is about khilafah. In his book, the title is al-Islam wa Usul al-Hukm: Bahs fi al-Khilafah wa al-Hukumah fi al-Islam, he argues that khilafah is not an obligation in Islam. It refers to the duty of the prophet Muhammad who is only obliged to convey Islam to people, not as king or leader of a State. This clearly makes many scholars deviate from his opinion. Therefore, it is important to discuss further related to the thought of Ali Abdul Raziq about the khilafah with the formulation of the problems, (1) Biography of Ali Abdul Raziq and (2) The thought of Ali Abdul Raziq about the khilafah. This study uses historical method with stages: heuristic, verification, interpretation, and historiography. The result of this research is that Ali Abdul Raziq through his book clearly states that the khilafah is not an obligation in Islam. This was influenced by the Western thoughts, he taked when he studied in England. This opinion ultimately resulted in him being ostracized among Egyptian scholars. Nevertheless, his thinking is widespread, as evidenced by the same pattern of thinking shared by several figures in Indonesia.Keywords: Ali Abdul Raziq, Khilafah, History, Thought.